Professional Management of Human Resources on Employee Performance: A Case Study at PT. Pos Indonesia - Subarjo (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2022)
Human resource management is a process for dealing with various problems within the scope of work in order to support the activities of an organization or company in order to achieve predetermined goals. Humans are one of the important elements in an organization, because humans are the driving force and determining the running of an organization. The elements of human resource management are individuals who are workers in the company. Thus, the focus studied by human resources is on issues affecting the human workforce. This research is included in the category of causal associative research using a quantitative approach. The results of this study are (1) Placement has a positive effect on the performance of the employe of PT. POS INDONESIA (PERSERO) Sleman Branch. (2) Workload has a negative effect on the performance of the employees of PT. POS INDONESIA (PERSERO) Sleman Branch. (3) Compensation has a positive effect on the performance of employees of PT. POS INDONESIA (PERSERO) Sleman Branch.